Meningkatkan Motivasi Belajar Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe NHT - Sholehah, Sholehah; Jamal, M. Arifuddin (Universitas Lambung Mangkurat, 2013)
This research relates to the implementation of NHT in State Senior High School 12 (SMAN 12) Banjarmasin. The research objective is to describe that: (1) the Lesson Plan is well implemented; (2) social skill; (3) motivation on learning; (4) the learning result; (5) as well as the studentsâ response through the learning process. This research is Classroom Action Research (CAR) of Hopkins model which is divided in 3 phases. To collect the data of this research is using questioners, observation, test, and documentation. The data is analyzed descriptively qualitatively and quantitavely. The result of the research: (1) the Lesson Plan that implemented in the faze 1 is 88,25%,, II 97,75%, and III 100% with very good result; (2) The studentsâ social skill enhance in every phase; (3) student motivation on learning in phase I for the attention and satisfaction aspects was in good category, aspects of relevance and confidence category was in quite good, phase II of all aspects was in good category, but aspect of confidence was still in pretty good category, and the phase III of all aspect was in good category; (4) the result of the studentsâ learning classically enhanced, in phase I is about 45% (not passed), II 83% (ot passed), and III 100% (passed); (5) the response of interest to follow cooperative learning is good category. To obtain the conclusion that the application of cooperative learning type NHT can enhance students motivation.Â